Comparison of Two Stifle Exploratory Methods Using Mini-Arthrotomy for Diagnosis of Canine Medial Meniscal Pathology: An Ex Vivo Study - Kmieciak, Lauren A.; Aulakh, Karanvir S.; Harper, Tisha A.M.; Mitchell, Mark A.; Butler, Ryan J.; Liu, Chin-Chi; Aulakh, Harmeet K. (Veterinary and Comparative Orthopaedics and Traumatology, 2022)
Objective The main aim of this study was to compare the accuracy of stifle exploratory using either a stifle distractor (SD method) or a combination of Hohmann and Senn retractors (HS method) for diagnosing canine medial meniscal tears in cranial cruciate ligament-deficient stifles.Study Design Fifteen pairs of canine cadaveric pelvic limbs were used and cranial cruciate ligament were transected in all stifles. Paired limbs were then randomly assigned to one of five groups based on the tears created in the caudal pole of the medial meniscus: no tear, peripheral detachment, or a variation in three vertical longitudinal tears. A craniomedial mini-arthrotomy was performed by two observers and diagnosis of the medial meniscal status was made utilizing the HS and SD methods. Correct diagnosis of the meniscal tear was compared for both methods and observers.Results Correct diagnoses were made using the HS and SD methods in 24/30 and 24/30 cases for observer 1 respectively; and in 17/30 and 19/30 cases for observer 2 respectively. There was no significant difference in the correct diagnosis of meniscal tears within each observer between the two methods.Conclusion Both HS and SD methods have equal accuracy for the diagnosis of canine medial meniscal pathology for a board-certified surgeon. Unassisted surgeons using the SD method for the evaluation of the medial meniscus are at no diagnostic disadvantage compared with assisted surgeons utilizing the HS method.
Keywords: meniscal tear; stifle distractor; Hohmann retractor; dogs